Pengaruh Kompetensi Aparatur Desa, Komitmen Organisasi dan Partisipasi Masyarakat Terhadap Pengelolaan Dana Desa (Kasus Gampong Cot Nga Kecamatan Peusangan Kabupaten Bireuen) - Hadi, Saiful; Syahriani, Endang (Aceh Cooperative Care, 2022)
The research was conducted in the people of Cot Nga Village, Peusangan District, Bireuen Regency with a sample of 270 local people. The research is in the form of a case study on the factors that influence the management of village funds, using an associative descriptive method and a statistical analysis tool, namely the path analysis model. Data collection used a closed questionnaire to the respondents who were determined based on purposive sampling. The research results show that; 1) there is a direct and indirect positive influence on the competence of village officials on village fund management of 39.28%, (2) there is a direct and indirect positive effect on organizational commitment to village fund management of 51.92%. (3) there is a significant direct and indirect effect of community participation on village fund management of 40.72%. (4) Simultaneously apparatus competence, organizational commitment and community participation influence the management of village funds with a contribution of 52.3%.